DEVELOPING A CULTURE OF COOPERATION FOR ELEMENTARY SCHOOL STUDENTS - Xasanova Zaynabxon Shavkatjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article sheds light on the formation of a culture of cooperation among primary school students and the formation of a positive and harmonious environment at school.